The effects of male migration on irrigation systems in Nepal - Pradhan, Prachanda; Meinzen-Dick, Ruth S.; Zhang, Wei (International Food Policy Research Institute, 2021)
Widespread male migration from rural areas is a major force shaping agrarian transformation in Nepal. One particularly important area affected is the governance and management of irrigation systems. The resilience of systems to the effects of male migration is likely to depend on whether (and how) the men’s contributions to the system are met. This highlights the importance of understanding how Water Users’ Associations' (WUAs) organizational functioning evolves, internal and external factors driving the evolution process, the extent of technical and institutional innovation, and the outcomes in terms of system functioning.